Versatile Dual Reporter Gene Systems for Investigating Stop Codon Readthrough in Plants - KAVANAGH, THOMAS; LAO, NGA THI (My University, 2009)
Background Translation is most often terminated when a ribosome encounters the first in-frame stop codon (UAA, UAG or UGA) in an mRNA. However, many viruses (and some cellular mRNAs) contain ?stop? codons that cause a proportion of ribosomes to terminate and others to incorporate an amino acid and continue to synthesize a ?readthrough?, or C-terminally extended, protein. This dynamic redefinition of codon meaning is dependent on specific sequence context. Methodology We describe two versatile dual reporter systems which facilitate investigation of stop codon readthrough in vivo in intact plants, and identification of the amino acid incorporated at the decoded stop codon. The first is based on the reporter enzymes NAN and GUS for which sensitive fluorogenic and histochemical substrates are available; the second on GST and GFP. Conclusions We show that the NAN-GUS system can be used for direct in planta measurements of readthrough efficiency following transient expression of reporter constructs in leaves, and moreover, that the system is sufficiently sensitive to permit measurement of readthrough in stably transformed plants. We further show that the GST-GFP system can be used to affinity purify readthrough products for mass spectrometric analysis and provide the first definitive evidence that tyrosine alone is specified in vivo by a `leaky? UAG codon, and tyrosine and tryptophan, respectively, at decoded UAA, and UGA codons in the Tobacco mosaic virus (TMV) readthrough context.
PUBLISHED
Keywords: Genetics